Analysis of factors affecting rural residents’ willingness to adjust energy use behaviors based on a multi-group analysis - Xi Luo; Min Zhang; Xiaojun Liu (Energy Reports, 2023)
The rural energy reform, which is caused by the rapid development of renewable energy, will significantly impact rural residents’ energy use behaviors. The willingness of rural residents to adjust energy use is critical for realizing the rural energy reform. In this study, a questionnaire survey was implemented to ask residents to consider three virtual electricity pricing scenarios and investigate residents’ willingness to adjust energy use behaviors. Scenario PVR (Peak–valley rate) involved applying the peak–valley rate electricity price. Scenario PVS (Photovoltaic systems) involved building photovoltaic systems. Scenario OFR (Original flat-rate) involved maintaining the original flat-rate electricity price. The extended theory of planned behavior was then used to conduct a multi-group analysis to assess the factors influencing rural residents’ willingness to adjust energy use. The field research results for 533 rural households in the Guanzhong Plain in China indicated that (1) The proportions of rural residents choosing Scenario PVR, Scenario PVS, and Scenario OFR were 45.22%, 22.89%, and 31.89%, respectively. (2) The rural residents choosing Scenario PVS and Scenario OFR showed the strongest and the weakest willingness to adjust energy use, respectively. (3) Social capital significantly affected residents’ attitude and perceived behavioral control about their willingness to adjust energy use; however, there is a discrepancy in the impact mechanism for different residents. (4) For rural residents choosing Scenario PVS, their willingness to adjust energy use was significantly affected by policies and regulations; the impact was less significant for residents choosing the other scenarios.